The effectiveness of task-based language teaching to improve cadets’ critical thinking skills in comprehending ESP English text - Wibowo, Amiruddin Hadi; Munir, Ahmad; Suhartono, Suhartono (Edelweiss Applied Science and Technology, 2024)
Reading is crucial for English learners to enhance their fluency, vocabulary, and overall academic success, especially in terms of reading comprehension. In the context of English for Specific Purposes (ESP), critical thinking is particularly important for cadets as it enables them to engage with specialized content, such as maritime studies. This study examines the effectiveness of Task-Based Language Teaching (TBLT) in improving cadets’ critical thinking skills and reading comprehension of ESP reading texts. This study used quantitative research design. The subjects were 64 cadets and two lecturers at a Merchant Marine Polytechnic in Surabaya. Data were collected using observations, interviews, and pretest-posttest results and analyzed using descriptive statistics, t-tests, and MANOVA to assess cadets’ critical thinking and reading comprehension before and after implementing TBLT. The results of MANOVA showed a significant improvement in critical thinking skills and reading comprehension among cadets using the TBLT model compared to those who did not. The TBLT improved cadets' abilities to analyze, evaluate, and apply ESP content to practical maritime contexts. The significance value of the Hotelling’s Trace test (p < 0.05) confirmed the positive impact of TBLT on both skills. In conclusion, TBLT effectively improves critical thinking and reading comprehension skills in ESP learning for cadets. These findings emphasize use of TBLT to develop critical academic skills, providing a strong foundation for learners in specialized areas such as maritime studies.